Effects of Multicomponent Exercise on Functional and Cognitive Parameters of Hypertensive Patients: A Quasi-Experimental Study - Hélio José Coelho Junior; Bruno Rodrigues; Daniele Jardim Feriani; Ivan de Oliveira Gonçalves; Ricardo Yukio Asano; Samuel da Silva Aguiar; Marco Carlos Uchida (Journal of Aging Research)
Purpose. The present study aimed to investigate the impact of a 6-month multicomponent exercise program (MCEP) on physical function and cognitive parameters of normotensive (NTS) and hypertensive (HTS) older patients and verify if age can influence the adaptations in response to the exercise. Methods. A total of 218 subjects, 101 NTS and 117 HTS, were recruited and underwent functional and cognitive evaluations before and after six months of a MCEP. The program of exercise was performed twice a week, for 26 weeks. The physical exercises were thought to mimic the activities of daily living and, therefore, aggregated functional and walking exercises. Exercise sessions were performed at moderate intensity. Results. Data indicated that HTS and NST patients showed a similar increase in the performance of walking speed test and one-leg stand test after the MCEP. Regarding age, results did not show differences in the magnitude of adaptations between old and young HTS and NTS patients. Conclusions. Data of the present study indicated that a 6-month MCEP was able to increase equally balance and mobility in NTS and HTS patients. Moreover, data demonstrated that aging did not seem to impair the capacity to adapt in response to exercise in both groups.